Implementasi Aktivasi Identitas Kependudukan Digital (Ikd) Dalam Mendorong Digitalisasi Di Kelurahan Jepara Kota Surabaya - Agus Widiyarta; Isni Humaidah (Peneliti.net, 2023)
The Digital Population Identity Application (IKD) which has been issued by the Directorate General of Population and Civil Registration of the Ministry of Home Affairs is one of the innovations as well as an adaptation during the transitional period in the development of digitalization in Indonesia. One of the cities implementing digitalization is the city of Surabaya. Surabaya City is one of the cities in East Java Province which consists of 31 sub-districts and has 154 sub-districts in it. One of them is Jepara Village. With so many residents in the city of Surabaya, automatically every day there are always problems related to population administration, one of which is the limited availability of E-KTP blanks. This problem is the basis for the application of Digital Population Identity (IKD). This study aims to determine the Implementation of Digital Population Identity (IKD) Activation in Encouraging Digitalization in Jepara Village, Surabaya City with the Policy Implementation model by George C. Edward III. The research method used in this study is descriptive qualitative using data collection techniques in the form of observation and documentation. The results of this study indicate that the Jepara Village has carried out the entire activation process according to the procedure. However, in order to maximize or improve related performance, there is a need for continuous outreach to increase citizens to activate Digital Population Identity (IKD).